Exploring Teachers' Perceptions and Implementation of AI in English Language Teaching - Asgap, Muhammad Syarif; Khatimah, Khusnul (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The integration of Artificial Intelligence (AI) in education has gained considerable attention for its potential to enhance teaching and learning experiences. This study examines the perceptions and practices of English teachers in Samarinda, East Kalimantan, regarding AI integration in English language teaching. Data were collected from 145 English teachers across public and private secondary schools using a structured questionnaire covering demographic information, perceptions of AI, and current AI integration practices. The findings indicate that most teachers hold a positive outlook on AI, with 65% recognizing its potential benefits, such as improving student engagement and personalized learning. However, challenges remain, as 55% of respondents expressed concerns about the complexity of AI tools, while 45% feared potential job displacement. Although 58% of teachers reported using AI tools, only 20% fully integrated AI into their daily teaching routines. Further analysis highlights that demographic factor, such as teaching experience and prior AI training, significantly influence teachers’ readiness to adopt AI. Teachers with more experience and relevant training exhibited greater confidence and a higher tendency to integrate AI tools effectively. These findings emphasize the need for targeted professional development programs to support AI adoption in English language teaching.